Serum titres of anti-glutamic acid decarboxylase-65 and anti-IA-2 autoantibodies are associated with different immunoregulatory milieu in newly diagnosed type 1 diabetes patients - Andrade Lima Gabbay, M.; Sato, M. N. [UNESP]; Duarte, A. J. S. [UNESP]; Dib, S. A. (Wiley-Blackwell, 2012)
Several studies correlated genetic background and pancreatic islet-cell autoantibody status (type and number) in type 1A diabetes mellitus (T1AD), but there are no data evaluating the relationship among these markers with serum cytokines, regulatory T cells and beta cell function. This characterization has a potential importance with regard to T1AD patients' stratification and follow-up in therapeutic prevention. In this study we showed that peripheral sera cytokines [interleukin (IL)-12, IL-6, II-1 beta, tumour necrosis factor (TNF)-a, IL-10] and chemokines (CXCL10, CXCL8, CXCL9, CCL2) measured were significantly higher in newly diagnosed T1AD patients when compared to healthy controls (P < 0.001). Among T1AD, we found a positive correlation between CXCL10 and CCL-2 (r = 0.80; P = 0.000), IL-8 and TNF-alpha (r = 0.60; P = 0.000); IL-8 and IL-12 (r = 0.57; P = 0.001) and TNF-alpha and IL-12 (r = 0.93; P = 0.000). Glutamic acid decarboxylase-65 (GAD-65) autoantibodies (GADA) were associated negatively with CXCL10 (r = -0.45; P = 0.011) and CCL2 (r = -0.65; P = 0.000), while IA-2A showed a negative correlation with IL-10 (r = -0.38; P = 0.027). Human leucocyte antigen (HLA) DR3, DR4 or DR3/DR4 and PTPN22 polymorphism did not show any association with pancreatic islet cell antibodies or cytokines studied. In summary, our results revealed that T1AD have a proinflammatory cytokine profile compared to healthy controls and that IA-2A sera titres seem to be associated with a more inflammatory peripheral cytokine/chemokine profile than GADA. A confirmation of these data in the pre-T1AD phase could help to explain the mechanistic of the well-known role of IA-2A as a more specific marker of beta-cell damage than GADA during the natural history of T1AD.
Keywords: cytokine; pancreatic autoantibodies; regulatory T cells; type 1 diabetes